The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.29333/ejmste/108438
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends in Digital Technologies and Modeling in Mathematics Education

Abstract: This document presents a literature review that analyzes the articulation of modeling and digital technologies in the field of Mathematics Education. The review aims to find evidence of the use of digital technologies in modeling processes and how these practices can change some ways of working with students in the classroom. The results show, on the one hand, different roles that technology plays when it is articulated to a modeling process (as a resource in the process or as a means that reorganizes the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
3
14
0
3
Order By: Relevance
“…As observed in Figures 3 and 4, even though the quantities A and V appear in the model, the variable that needed to be taken into account in the model was the ratio between them (A/V). According to Molina-Toro and colleagues [25], the software was used as a support for the mathematical activity of the students. The software allowed model analysis to have components of interpretation, exploration and manipulation of variables, as well as the identification of regularities and the establishing of relationships; in some episodes, it also allowed the manipulation of geometric objects to recognize relationships between the quantities involved.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in Figures 3 and 4, even though the quantities A and V appear in the model, the variable that needed to be taken into account in the model was the ratio between them (A/V). According to Molina-Toro and colleagues [25], the software was used as a support for the mathematical activity of the students. The software allowed model analysis to have components of interpretation, exploration and manipulation of variables, as well as the identification of regularities and the establishing of relationships; in some episodes, it also allowed the manipulation of geometric objects to recognize relationships between the quantities involved.…”
Section: Discussionmentioning
confidence: 99%
“…Daher and Shahbari (2015) found that the spreadsheets helped prospective teachers build the technological mathematical model, where the integration of the spreadsheets happened in different phases of building the model. Molina-Toro, Rendón-Mesa, and Villa-Ochoa (2019), by reviewing the literature on the role of technology in mathematical modelling, found that the literature pointed at technology support of the various modelling processes that constituted part of the modeling cycle. The reviewed literature suggested that there are two roles of technology in carrying out modelling activities in the classroom.…”
Section: The Role Of Technology In Mathematical Modellingmentioning
confidence: 99%
“…Según Molina-Toro et al (2019), los estudios futuros deberán centrarse no solo en múltiples herramientas tecnológicas o en el rendimiento de los estudiantes, sino también en cómo modelan, cómo dan sentido a sus conjeturas, cómo realizan sus experimentos, cuál es el impacto de las tecnologías digitales en ellos y cuáles son las características de las herramientas que seleccionan para abordar esos procesos. Aunque la literatura científica sobre m-learning se ha desarrollado recientemente, aún es escasa y se necesita más investigación teórica y empírica sobre el uso de dispositivos móviles en el modelado.…”
Section: Discusión Y Conclusionesunclassified
“…La vinculación de la tecnología a la enseñanza de las matemáticas impone un desafío para el docente, no solo por el hecho de que las tecnologías digitales hayan transformado y estén transformando las relaciones humanas (Westera, 2004), sino también, porque esta vinculación parece servir de mediadora en la resignificación del proceso de enseñanza y aprendizaje (Inayat & Hamid, 2016). Se destacan dos perspectivas epistemológicas que pueden convivir en educación matemática: la primera concibe la tecnología como un recurso para el desarrollo de procesos de modelado; la segunda le asigna un rol reorganizador de este proceso, donde las tecnologías digitales son fundamentales para desarrollar experimentos y simulaciones que promuevan diversos tipos de participación de los estudiantes en la construcción de su propio conocimiento, al mismo tiempo que pueden acceder a soluciones numéricas, herramientas de visualización y control gráfico (Molina-Toro, Rendón-Mesa & Villa-Ochoa, 2019).…”
Section: Introductionunclassified